Peptide Synthesis - Varkey, Jaya T. (IntechOpen, 2019)
Peptide synthesis includes an array of techniques and procedures that enable the preparation of materials ranging from small peptides to large proteins. Many synthetic peptides have commercial and pharmaceutical applications, however, the synthesis of these peptides is a difficult task. This book addresses the common problems relating to the synthesis and applications of synthetic peptides. It discusses novel methods for the efficient synthesis of long chain and difficult peptide sequences and presents detailed analysis of various aspects of solid phase peptide synthesis. It also includes a section on antimicrobial peptides.